Flecainide-Associated Cardiogenic Shock in a Patient with Atrial Fibrillation. (18th November 2019) - Gjermeni, Erind; Bollmann, Andreas; Hindricks, Gerhard; Müssigbrodt, Andreas
Abstract : Flecainide is a frequently used antiarrhythmic drug, recommended by current guidelines as a first-line treatment option for restoring and maintaining sinus rhythm in patients with atrial fibrillation and no significant structural heart disease. In overdose, it can induce severe cardiogenic shock. Cardiogenic shock after a therapeutic dose of flecainide in patients without contraindication has not yet been reported in literature. Case Summary . We report a case of flecainide-associated cardiogenic shock in a 52-year-old woman with paroxysmal atrial fibrillation after a therapeutic dose of flecainide. Pharmacological cardioversion of symptomatic tachyarrhythmic atrial fibrillation with flecainide was unsuccessful and shortly after, she developed cardiogenic shock with severely reduced LVEF. Electrical cardioversion was also unsuccessful. Coronarography was unremarkable, and the cardiac MRI showed no signs of inflammation or fibrosis. After amiodarone loading, she converted to SR. This rare but severe complication despite adequate treatment could be explained by increased susceptibility to negative inotropic effect of flecainide as a consequence of marked tachycardia. Therefore, cautious monitoring after new administration of flecainide or the administration of a higher dose is advisable.